2008
DOI: 10.1007/s10113-008-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying disturbance effects on vegetation carbon pools in mountain forests based on historical data

Abstract: Although the terrestrial carbon budget is of key importance for atmospheric CO 2 concentrations, little is known on the effects of management and natural disturbances on historical carbon stocks at the regional scale. We reconstruct the dynamics of vegetation carbon stocks and flows in forests across the past 100 years for a valley in the eastern Swiss Prealps using quantitative and qualitative information from forest management plans. The excellent quality of the historical information makes it possible to li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
(32 reference statements)
0
18
0
4
Order By: Relevance
“…Our total biomass results are also consistent with results of Erb (2004), who reported a PNV carbon mass of 12.4 kgC m −2 for Austrian forests. Furthermore, in a study where LPJ-GUESS was used locally for a valley in the Swiss Prealps, Gimmi et al (2009) also concluded that the actual biomass was slightly smaller than the assumed natural forest biomass.…”
Section: Situation For the Simulation Year 2000mentioning
confidence: 99%
“…Our total biomass results are also consistent with results of Erb (2004), who reported a PNV carbon mass of 12.4 kgC m −2 for Austrian forests. Furthermore, in a study where LPJ-GUESS was used locally for a valley in the Swiss Prealps, Gimmi et al (2009) also concluded that the actual biomass was slightly smaller than the assumed natural forest biomass.…”
Section: Situation For the Simulation Year 2000mentioning
confidence: 99%
“…Individual-based models were used to simulate the effect of wind events on local structure and forest dynamics (e.g., Rademacher et al, 2004;Papaik and Canham, 2006;Uriarte and Papaik, 2007). Similar approaches were incorporated into models operating at larger spatial scales (e.g., Moorcroft et al, 2001: ED;Gimmi et al, 2009). Spatially explicit forest landscape models (i.e.…”
Section: From Events To Disturbance Regime 421 Spatio-temporal Dynmentioning
confidence: 99%
“…in the valley bottom to the upper tree line at about 2 400 m a.s.l. These forests were chosen due to the excellent historical source availability, especially forest management plans which are a valuable source for reconstructing historic forest conditions and forest uses (Bürgi, 1999;Gimmi and Bürgi, 2007;Gimmi et al, 2009). …”
Section: Study Areamentioning
confidence: 99%